EFFECTS OF SODIUM-GLUCOSE COTRANSPORTER-2 INHIBITORS ON HEMATOCRIT AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS: A TERTIARY CENTER EXPERIENCE - Khoo, Jia Jun; Diah, Mohd Idris Mohamad; Nagaratnam, Shamharini; Tong, Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have become integral to managing Type 2 Diabetes Mellitus (T2DM) due to their cardiorenal benefits. They promote osmotic diuresis, leading to hemoconcentration and increased erythropoiesis, which may theoretically raise thromboembolic risk. Emerging data suggests these changes reflect improved renal function and support their benefits. This study aimed to assess the impact of SGLT2 inhibitors on haematocrit in our patients with T2DM. METHODOLOGY This retrospective observational study involved patients with T2DM initiated on SGLT2 inhibitors at our center between January 2024 and September 2024. Patients were included if they received continuous empagliflozin for more than 3 months. We collected data on hemoglobin (Hb) and hematocrit (Hct) levels at baseline and up to 6 months post-initiation. Erythrocytosis was defined according to the 2016 WHO criteria: Hb >16.5 g/dL and/or Hct >49% in men and Hb >16 g/dL and/or Hct >48% in women. RESULT This study included 88 patients with T2DM (45 men [51.1%], 43 women [48.9%]) with a median age of 62.0 years (IQR 53-70). The cohort had a median diabetes duration of 10.0 years (IQR 4-19) and a median baseline HbA1c of 7.9% (IQR 6.7-9.8). After a median follow-up of 6.0 months (IQR 6-9), we observed significant increases in hematologic parameters: hemoglobin (12.9 ± 1.8 to 13.5 ± 1.6 g/dL, p <0.001), hematocrit (40.10 ± 5.3% to 41.3 ± 4.7%, p <0.001), and RBC count (4.75 ± 0.77 to 4.98 ± 0.72 × 10¹²/L, p <0.001). HbA1c decreased by a median of 0.5% (IQR -1.0 to 0.0, p <0.001). Despite these hematologic changes, post-treatment erythrocytosis prevalence remained low at 5.7% (5/88), and no treatment discontinuation was required. CONCLUSION These findings demonstrate that while SGLT2 inhibitors predictably increase hematologic indices, the risk of clinically significant erythrocytosis remains low. The observed hematologic changes likely represent adaptive physiological responses contributing to empagliflozin’s cardiorenal protective effects.